KONTRIBUSI GURU BERPENDIDIKAN AKADEMIK STRATA 2 DAN PELATIHAN TERHADAP MUTU HASIL BELAJAR SISWA DI MTSN SE KABUPATEN TANAH DATAR - Jufri Jufri (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
the contribution of post graduate program (S2) and training toward students’ outcome quality of MTsN at Tanah Datar Regency.Research population were teacher of State Islamic Junior High School of Tanah Datar Datar Regency that were post graduate program (S2) and had followed training, they were 23 teachers.The result of data analyses show that a) post graduate program (S2) contributed significantly toward students’ outcome quality State Islamic Junior High School of Tanah Datar Datar Regency was (60,3%) .b) training contributed significantly toward students’ outcome quality State Islamic Junior High School of Tanah Datar Datar Regency was (51%) toward the teachers’ performance; c) post graduate program (S2) education and training contributed significantly toward students’ outcome quality of State Islamic Junior High School of Tanah Datar Datar Regency was (63,6%)Kata Kunci: Kontribusi guru, strata 2, pelatihan, mutu hasil belajar